1992
DOI: 10.1210/endo.130.5.1374017
|View full text |Cite
|
Sign up to set email alerts
|

Body growth, carcass composition, and endocrine changes in lambs chronically treated with recombinantly derived insulin-like growth factor-I.

Abstract: Castrate yearling male sheep were treated for 8 weeks with either 50 micrograms/kg body wt/8 hourly sc insulin-like growth factor-I (IGF-I) (n = 10) or with saline (n = 9). IGF-I treatment increased plasma IGF-I from 235 +/- 17 to 347 +/- 16 ng/ml (P less than 0.001). There was a gradual divergence in body wt (P less than 0.10) between treatment groups. Food intake did not change significantly. The weight of the spleen corrected for body wt increased by 40% (P less than 0.001) and there was a marginal increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 21 publications
2
23
1
Order By: Relevance
“…Because of these similarities in structure, a number of studies have examined the effects of IGF-I on both food intake and glucose metabolism in large animals. It now seems clear that recombinant IGF-I has no effect on food intake in sheep, either when infused directly into the ventricle for 6 days [24] or when delivered by subcutaneous injection for 56 days [14]. The sheep in the present study showed a large variation in intake; however, during the first week of infusion of LR3IGF-I there was an indication of a decline in voluntary intake recovering to pretreatment intake after 8-9 days of treatment.…”
Section: Discussioncontrasting
confidence: 50%
See 4 more Smart Citations
“…Because of these similarities in structure, a number of studies have examined the effects of IGF-I on both food intake and glucose metabolism in large animals. It now seems clear that recombinant IGF-I has no effect on food intake in sheep, either when infused directly into the ventricle for 6 days [24] or when delivered by subcutaneous injection for 56 days [14]. The sheep in the present study showed a large variation in intake; however, during the first week of infusion of LR3IGF-I there was an indication of a decline in voluntary intake recovering to pretreatment intake after 8-9 days of treatment.…”
Section: Discussioncontrasting
confidence: 50%
“…This suggests a direct response of insulin to circulating LR3IGF-I which over-rides any response to the initial reduction in endogenous IGF-I. A direct effect of IGF-I on insulin is reported in other studies by which treatment with IGF-I reduces plasma insulin concentrations when euglycaemia is maintained in dogs [6], rats [7], humans [8] and, in association with an increase in plasma glucose, sheep [14].…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations